Implementasi Kurikulum Merdeka Pada Sekolah Menengah Pertama - Febrianti, Yanti; Nabila As-Salafy, Shofa; Hidayat, Sholeh (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The Merdeka Curriculum offers a variety of extracurricular activities with content that is designed to give students enough time to enhance their competencies and understand ideas in greater depth. Instructors are free to select the resources they use to teach, and this change is being implemented with the goal of raising educational standards by emphasizing the Pancasila student profile. In keeping with Ki Hadjar Dewantara's ideology, every kid has the chance to reach their full potential through the Merdeka Curriculum. Through an analysis of numerous works pertaining to the implementation of the Independent Curriculum, the research approach makes use of literature study. The shift has resulted in the adoption of new paradigms, the digitization of classrooms, and the enhancement of Pancasila students' (P5) profile via the completion of several theme-based projects. The implementation of positive culture, differentiated instruction.